2010
DOI: 10.2967/jnumed.110.079566
|View full text |Cite
|
Sign up to set email alerts
|

Early Repeated 18F-FDG PET Scans During Neoadjuvant Chemoradiation Fail to Predict Histopathologic Response or Survival Benefit in Adenocarcinoma of the Esophagus

Abstract: This study evaluated the role of 18 F-FDG PET as an early predictor of histopathologic response to neoadjuvant chemoradiotherapy and overall survival in patients with adenocarcinoma of the esophagus undergoing multimodal therapy. Methods: Thirty-seven patients with locally advanced adenocarcinoma of the esophagus underwent pretreatment and an intratreatment 18 F-FDG PET scan in the second week of a 6-wk regimen of neoadjuvant chemoradiotherapy. Histopathologic response and overall survival were correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
1
37
2
2
Order By: Relevance
“…The study by Wieder et al [7], in 38 patients with squamous cell carcinoma, also found an association between metabolic tumour response and OS. In contrast, the study by Malik et al [8], in 37 patients with adenocarcinoma, did not find a significant association.…”
contrasting
confidence: 51%
See 4 more Smart Citations
“…The study by Wieder et al [7], in 38 patients with squamous cell carcinoma, also found an association between metabolic tumour response and OS. In contrast, the study by Malik et al [8], in 37 patients with adenocarcinoma, did not find a significant association.…”
contrasting
confidence: 51%
“…Increased 18 F-FDG uptake caused by radiation-induced inflammation may limit the use of 18 F-FDG PET, because 18 F-FDG PET is unable to distinguish whether tracer uptake is associated with inflammatory cells or residual viable tumour cells [7,8]. To our knowledge, there are only three published prospective studies [7][8][9] in which the predictive value of early interim 18 F-FDG PET in patients who received concurrent neoadjuvant chemoradiotherapy has been investigated. These studies all demonstrated an association between a decrease in tumour standardized uptake value (SUV) 14 days after start of neoadjuvant treatment and histopathological tumour response [7][8][9].…”
mentioning
confidence: 96%
See 3 more Smart Citations